Pertanggungjawaban Pidana yang Menyalahgunakan Senjata Api Anggota POLRI - Arifin, Wisnu; Cahyo, Cahyo (Neolectura, 2023)
The Police are all matters relating to the functions and institutions of the police in accordance with statutory regulations. In carrying out the duties and positions of a member of the Indonesian National Police, he is given responsibility for the use of firearms, the firearms in question are weapons that can be carried anywhere. Sometimes in carrying out their duties and positions there are several members of the police who misuse the use of weapons. This study aims to find out how big the criminal responsibility of polri members who misuse firearms is in law number 2 of 2002 concerning the Indonesian National Police. This study uses an empirical juridical writing method, namely an approach to the problem and is connected with the facts in the problems encountered.